Emergence of Protoplanetary Disks and Successive Formation of Gaseous Planets by Gravitational Instability - Inutsuka, Shu-ichiro; Machida, Masahiro N; Matsumoto, Tomoaki (Astrophysical journal. Letters, 2010)
We use resistive magnetohydrodynamical (MHD) simulations with the nested grid technique to study the formation of protoplanetary disks around protostars from molecular cloud cores that provide the realistic environments for planet formation. We find that gaseous planetary-mass objects are formed in the early evolutionary phase by gravitational instability in regions that are decoupled from the magnetic field and surrounded by the injection points of the MHD outflows during the formation phase of protoplanetary disks. Magnetic decoupling enables massive disks to form and these are subject to gravitational instability, even at {approx}10 AU. The frequent formation of planetary-mass objects in the disk suggests the possibility of constructing a hybrid planet formation scenario, where the rocky planets form later under the influence of the giant planets in the protoplanetary disk.